Preparation and characterization of porous HA/β-TCP biphasic calcium phosphate derived from butterfish bone. (24th August 2022) - Deng, Kehan; Chen, Haiwen; Dou, Wenxue; Cai, Qi; Wang, Xingang; Wang, Shaohai; Wang, Dalin
ABSTRACT: HA/β-TCP biphasic calcium phosphate (BCP)ceramic materials have a wide application prospect in bone remodeling surgery as bone substitutes. This study extracted BCP from butterfish bone that was calcined at 700–1100 °C. Then, their composition and microstructure was characterized by X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR), inductively coupled plasma optical atom emissions spectroscopy (ICP-OES), scanning electron microscopy (SEM), and mercury intrusion porosimeter (MIP). The data showed that BCP containing hydroxyapatite (HA) and β-tricalcium phosphate (β-TCP) can be produced when the butterfish bone is calcined at >800 °C. The calcined butterfish bone contains a variety of trace metal elements. Taken together, the BCP material produced by calcination of butterfish bone above 800 °C shows a concentrated distribution of macropores and micropores, high porosity and nanograin size. Furthermore, it has a wide range of sources and is green and environmental-friendly, which is a potential source of BCP material.